Foraging ecology of feral goats on the Isle of Rum, NW Scotland - Shi, J; Dunbar, R (2009)
We studied foraging ecology of feral goats (Capra hircus) on the Isle of Rum, Scotland, from June to November 2000. Grazing bout length varied greatly from 1 min to 460 min with mean duration being 103. 1 ± 15. 0 (SD) min. Adult males and females differed marginally significantly in feeding bout length with females having relatively longer feeding bouts (P=0.077). The average bite rate for feral goats was 46. 3 ± 0. 6 bites/min with significant variations between sexes (P=0.023) and among months ( P < 0.001). Adult males had faster bite rates during pre- (June-July) and post-rutting (October-November) periods than during rutting period ( August-September) ( P < 0.008) , but the bite rate of adult females during pre-rutting period was not different from that during rutting period (P=0.327). Adult males also spent significantly less daytime feeding during rutting period. The differences in bite rates and feeding time between the two sexes might result in sexual differences in forage intake by feral goats : females had relatively stable intake, but males fluctuated greatly in their forage intake. The estimated forage intake decreased from June to November (although a slight increase from September to November) , which means that feral goats on Rum may be in negative energy balance during autumn/winter period when the quality of forage is lower and the weather is beginning to deteriorate. There was no significant difference in step rate while feeding between sexes or among months.